2009
DOI: 10.17851/2237-2083.17.1.7-50
|View full text |Cite
|
Sign up to set email alerts
|

Communication Strategies and Proficiency Levels in L2 Speech Production: a systematic relationship

Abstract: This study investigates the relationship between the use of Communication Strategies (CSs) and the proficiency level of L2 1 learners. In order to pursue this objective, three speech samples of 30 English L2 learners were collected over a period corresponding to an academic semester. Participants consisted of three groups of 10 learners each and were selected from three different proficiency levels: pre-intermediate, intermediate, and advanced. Three oral narratives were used to elicit learners' L2 oral produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
6
8
0
Order By: Relevance
“…For instance, Candidate 6 in the intervention group used 348 words (group level mean = 450), while Candidate 4 in the comparison group, who was also a grade level 5 student, used 281 words (group level mean = 386). This finding is supported by other studies showing that high proficiency level students use fewer CSs (Chen 1990;Prebianca 2009). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For instance, Candidate 6 in the intervention group used 348 words (group level mean = 450), while Candidate 4 in the comparison group, who was also a grade level 5 student, used 281 words (group level mean = 386). This finding is supported by other studies showing that high proficiency level students use fewer CSs (Chen 1990;Prebianca 2009). …”
Section: Discussionsupporting
confidence: 84%
“…However, the limited sample sizes (n = 22 and n = 13) may have been a restraining factor in this respect. Other studies have indicated that higher proficiency level students may be prone to using fewer strategies (Chen 1990;Prebianca 2009), as also evidenced in this study. Apart from this finding, the analyses yielded mixed and contradictory results.…”
Section: Discussionsupporting
confidence: 82%
“…Research in this area has focused on investigating the use of CSs in relation to various factors, such as the learners' proficiency level (Bialystok & Fröhlich, 1980;Paribakht, 1984;Safont Jorda, 2001;García Núñez, 2006;Prebianca, 2009) and the task used for elicitation purposes (Poulisse & Schils, 1989;Rabab'ah & Seedhouse, 2004). Consideration has also been given to the influence of the learners' L1 (Fernández Dobao, 2001;Rabab'ah & Bulut, 2007), the situational context in which the CSs are employed (Williams, Inscoe & Tasker, 1997) as well as the learning context (Lafford, 2004), amongst others.…”
Section: Previous Research and The Proficiency Factormentioning
confidence: 99%
“…The empirical studies which have focused on the proficiency factor have demonstrated a relationship between learners' proficiency levels and their use of CSs (Fernández Dobao, 2001Safont Jordá, 2001;Littlemore, 2003;García Núñez, 2006;Prebianca, 2009). It has been observed that those learners with a lower level of L2 competence need to resort to a higher number of CSs due to the relatively small number of linguistic resources available.…”
Section: Previous Research and The Proficiency Factormentioning
confidence: 99%
See 1 more Smart Citation